Another new species of Dibamus Duméril & Bibron, 1839 (Squamata: Dibamidae) from Nui Chua National Park, Ninh Thuan Province, Vietnam - Kliukin, Nikita S.; Bragin, Andrey M.; Nguyen, Tan Van; Le, Son Xuan; Tran, Tin Trong Vo; Gorin, Vladislav A.; Poyarkov, Nikolay A. (Zootaxa, 2024)
A new species of dibamid lizard, Dibamus deimontis sp. nov., is described based on eight specimens collected from the highlands of Nui Chua Mountain within Nui Chua National Park, Ninh Thuan Province, southern Vietnam. Dibamus deimontis sp. nov. co-occurs with the recently described Dibamus tropcentr, but is recorded at higher elevations (670–700 m a.s.l. vs. 200–280 m a.s.l.), and in a different habitat and microhabitats than the previous species. Our study represents the first report on the near sympatric occurrence of two Dibamus species. The new species can be distinguished from other congeners by the following combination of characters: rostral, labial and nasal sutures incomplete; two to three postoculars; three to five scales on the posterior edge of infralabial; 22–25 midbody scale rows; 193–225 ventral scales; 47–55 subcaudal scales; 115 presacral and 27 tail vertebrae (in a single male specimen examined); and maximum snout-vent length 136.2 mm. We suggest this species should be considered as Vulnerable (VU) following the IUCN’s Red List categories. Our study brings the number of species in the genus Dibamus to 26; Dibamus deimontis sp. nov. is the eighth species of Dibamus recorded in Vietnam, and underlines the importance of the country as a local center of reptilian diversity in Southeast Asia.